Microbiological, serological and molecular diagnosis of abscess of withers in equine in the State of Pará (Research, Society and Development, 2021)
There are several infectious diseases that affect equines and can cause large economic losses in this sector and damage to animal welfare. In this species, abscessing lesions of a purulent character preferentially in the withers are strongly suggestive of brucellosis. However, few studies have been carried out on the disease in this species, making its identification and control difficult due to the lack of standardization in the interpretation of results. Therefore, samples of whole blood, serum and purulent secretion were collected from three horses. The animals came from the state of Pará. The diagnostic methods selected were the Rose-Bengal plate test (RBPT) and Polymerase Chain Reaction (PCR), for the negative molecular results for brucellosis, microbiological analysis were chosen. Although part of the samples were positive for brucellosis in serological tests, all of them showed negative results for PCR. In bacterial cultivation, species were isolated Streptococcus equi subsp. zooepidemicus, Enterococcus faecalis e Staphylococcus sciuri subsp. lentus., which showed resistance to antibacterials, especially the E. faecalis isolate classified as MDR (multi drug resistant). In conclusion, the best form of diagnosis is the joint evaluation of several tests, both screening and confirmatory, in order to obtain a definitive diagnosis with assertiveness.